2005
DOI: 10.1111/j.1365-2591.2005.00979.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro peroxide penetration into the pulp chamber from newer bleaching products

Abstract: The peroxides from the whitening strip and paint-on whiteners penetrated into the pulp chamber to varying degrees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 17 publications
4
48
0
9
Order By: Relevance
“…14 Despite the occurrence of the diffusion of the bleaching subproducts through the dentin, 22,23 the radicals present on the dentin are probably incapable of affecting the curing of the resin adhesives, reducing the bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…14 Despite the occurrence of the diffusion of the bleaching subproducts through the dentin, 22,23 the radicals present on the dentin are probably incapable of affecting the curing of the resin adhesives, reducing the bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, doses of 10 and 15 J/cm 2 were not capable of producing any effect on the activity of the protein evaluated. These results may be explained, at least in part, by a specific phenomenon known as "biphasic dose response" or "hormesis" (the Arndt-Schulz law) [42].…”
Section: +mentioning
confidence: 99%
“…Since the tooth-bleaching process is mediated by ROS, which can diffuse through the enamel and dentin, reaching the pulp space [2], these aesthetic procedures can promote pulp alterations, such as mild inflammation or even partial necrosis [3][4][5]. Due to the deleterious effects caused by components of bleaching agents, which have been demonstrated in both in vitro [6][7][8][9][10] and in vivo studies [3,5,11], the evaluation of other bleaching techniques that can prevent or reduce pulp damage is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Low-concentration HP (15-20%) gels for in-office therapy provide effective bleaching associated with less intense and prevalent tooth sensitivity (5,6). The CP-based gels have the advantage of promoting a slow and gradual release of HP, which prevents its quick diffusion through enamel and dentin at high concentrations (7). The 10% CP gel has been considered a safe bleaching technique for tooth structure, since several studies demonstrated low incidence of post-operative sensitivity (8) and low trans-enamel and trans-dentinal cytotoxicity (4).…”
Section: Introductionmentioning
confidence: 99%